Male Holstein calves fed a milk replacer and pelleted calf starter containing a botanical extract or a direct-fed microbial alone or in combination - Lydia K. Olagunju; David P. Casper; Michael Officer; Keith Klanderman; Uchenna Y. Anele (Journal of Dairy Science)
ABSTRACT: Botanical extracts (BE; Apex, Adisseo North America, Atlanta, GA) are known to enhance DMI and gut health, whereas direct-fed microbials (DFM), such as a Lactobacillus acidophilus fermentation product (EX: Excel; Pacer Technology Inc., Murtaugh, ID), have demonstrated improved gut health and growth performance when fed to growing neonatal Holstein calves. The hypothesis was this combination may be synergistic to neonatal calf growth performance and intestinal health. Eighty Holstein bull calves aged 2 to 5 d were blocked by BW and randomly assigned to 1 of 4 treatments arranged using a randomized complete block design. Treatments were as follows: (1) control, no additives; (2) BE added at 496 mg/kg to the calf starter (CS); (3) EX added to the CS at 2.50 g/kg with EX added to the milk replacer (MR) at 5 g/d; and (4) BE+EX: BE and EX added to CS at same rates and added EX to MR. Calves received 0.283 kg of MR in 1.9 L fed 2×/d for the first 14 d, then increased to 0.42 kg in 2.84 L fed 2×/d through d 35, followed by 0.42 kg of MR in 2.84 L fed 1×/d through d 42, followed by weaning. The CS was a 25% CP DM basis mini-pellet and the MR was a 22:20 (CP:fat) fed 2×/d at 0630 and 1800 h along with free choice water. Weaning occurred after d 49 of the 70-d experiment. Calves fed CS EX alone demonstrated greater BW gain compared with calves fed BE+EX, with calves fed control and BE being intermediate and similar (63.9, 63.5, 65.0, and 59.7 kg for control, BE, EX, and BE+EX, respectively). Total DMI (MR+CS) was lower for calves fed BE+EX compared with calves fed the remaining treatments (116.5, 114.2, 116.4, and 104.9 kg). The feeding of a BE in combination with EX (DFM) to neonatal calves reduced BW during wk 8, 9, and 10 and reduced 0 to 70 d ADG (874.7, 870.0, 889.7, and 817.6 g/d) compared with calves fed the remaining treatments. Calves fed BE+EX demonstrated the lowest calf starter intake during wk 4 through 10 compared with calves fed the other treatments. The study average CS intake for calves fed control and EX was greater compared with calves fed BE+EX with calves fed BE being similar and intermediate. Calves fed EX and BE+EX demonstrated greater total days of fecal scour score = 1 (5.4, 5.7, 8.0, and 8.3 d) compared with calves fed control and BE. Gains in frame measurements of hip height, hip width, withers height, and body length were similar whereas calves fed BE+EX demonstrated lower heart girth gains (19.2, 18.3, 19.7, and 17.6 cm) during the milk feeding phase (0–7 wk) compared with calves fed control and EX, with calves fed BE being similar and intermediate. It is not known why this study demonstrated an antagonism between BE and EX in growth performance and feed intake but further research is needed to identify the mechanism of action.